1984
DOI: 10.1159/000215110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prostacyclin (Epoprostenol) on the Aggregation of Human Platelets in Whole Blood in vitro

Abstract: Prostacyclin (PGI2) is a potent endogenous inhibitor of platelet aggregation. The effect of PGI2 on platelet aggregation and disaggregation in whole human blood was studied at 37 °C in vitro. Aggregation or disaggregation was quantified by counting single platelets using the recently developed Ultra Flo 100 Whole Blood Platelet Counter. Aggregation of platelets in whole blood was induced by arachidonic acid (AA, 400 μM), adenosine 5’-diphosphate (ADP, 10 μM), thrombin (0.1 U/ml) and colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…We have confirmed previous reports that ZK 36374 inhibits platelet aggregation in a dose-dependent fashion after in vitro addi tion to PRP and whole blood [10,16]. There was variability in responsiveness to the drug within our study group as reflected by the widely differing percent inhibition of aggre gation observed in each of the volunteers.…”
Section: Discussionsupporting
confidence: 90%
“…We have confirmed previous reports that ZK 36374 inhibits platelet aggregation in a dose-dependent fashion after in vitro addi tion to PRP and whole blood [10,16]. There was variability in responsiveness to the drug within our study group as reflected by the widely differing percent inhibition of aggre gation observed in each of the volunteers.…”
Section: Discussionsupporting
confidence: 90%
“…Although our data show upregulated FAO in PH platelets, we did not observe a significant increase in platelet activation markers. This is potentially due to the majority of our cohort being treated with PC, which have been demonstrated to directly inhibit platelet activation (41)(42)(43). Further study is required to define the lipid profile of platelets from PH patients and to determine whether (in the absence of medication) altered platelet bioenergetics are linked to changes in platelet function in PH.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies in which human platelets were incubated with ZK 36 374 de monstrated that the drug may be an even more power ful antiaggregating agent than PGI2 [8,10,11]. Fur ther, in human whole blood aggregation studies, ZK 36 374 caused disaggregation of preformed platelet aggregates [12].…”
Section: Discussionmentioning
confidence: 99%